Study on Artificial Intelligence, Analytics and Agile: Transforming Project Management in the 21st Century - Shivani Gupta (Recent Progress in Science and Technology Vol. 1, 2023)
There are a number of issues that have arisen as a result of the introduction of intricate and advanced technology, processes, and automation. Agile, analytics, and artificial intelligence all work together to improve project management as a discipline through ongoing development and reliable execution. This article expands on this subject by demonstrating how project management is being improved through the use of AI-supported tools, substantial data analytics, and the Agile methodology. Although technology is revolutionizing project management, project managers’ importance cannot be understated because they are the project’s main drivers and deliverers of value.